Exploration of Perceived Behavioral Control and Intention to Purchase to Increase Actual Behavior - Amanda, Tasya Aulia; Marsasi, Endy Gunanto (Image : Jurnal Riset Manajemen, 2024)
This study aims to determine whether perceived behavioral control and intention to purchase can increase actual behavior towards product purchases in generations Y and Z using the theory of planned behavior (TPB). This research uses a quantitative approach with a purposive sampling technique. The data type used is primary data, with collection techniques using questionnaires distributed to 215 respondents. This research uses Structural Equation Modeling (SEM) analysis with AMOS 24 Graphics software. The findings of this study indicate that utilitarian value, hedonic value, and trust have a significant positive effect on intention to purchase, subjective norms has a significant positive effect on perceived behavioral control, and intention to purchase has a significant positive effect on actual behavior. New findings in this study are that perceived behavioral control has a significant positive effect on the intention to purchase, and the subjective norms has a significant negative effect on the intention to purchase. This research can be useful for companies in optimizing marketing strategies by maintaining brand image, product innovation, and creating good perceptions with consumers. This study has a variable update, namely perceived behavioral control.